Staged Knee Arthrodesis Using Unilateral Locked Compression Plating: A Treatment for Recurrent Chronic Knee Infection. Issue 2 (12th June 2022) - Friedman, Lisa G.M.; Rothberg, David; Horwitz, Daniel S.
Abstract : Background: The treatment following massive infection of the knee remains a difficult problem with above knee amputation and knee fusion being available treatment options when revision arthroplasty is no longer possible. We present a series of 12 patients who underwent fusion using a staged protocol. Methods: The patients underwent a first stage involving removal of implants, debridement, and placement of an antibiotic space over a tibial nail. Stage II involved removal of the spacer and nail by fragmenting the cement, and re-debridement. A laterally based locked compression plate was used to achieve fusion. Results: There were no intraoperative complications. All patients achieved radiographic fusion. The average limb length discrepancy was 2.6 cm. Five patients required further surgery: 1 for drainage of a postoperative hematoma, 3 for persistent infectious symptoms, and 2 for implant irritation. At final follow-up 1 patient had persistent infection and was unable to ambulate. All other patients returned to ambulation with 4 utilizing assistive devices at final follow-up. Conclusion: Failed, infected total knee arthroplasty is a challenging problem without an easy solution. A variety of techniques for knee arthrodesis, including intramedullary nailing and external fixation have been described with a wide success rate ranging from 20% to 100%. Few studies have examined compression plating to achieve knee arthrodesis. The use a 2-stage, single locked compression plate technique to achieve arthrodesis for the treatment of chronic infection after failed revision total knee arthroplasty can be a highly successful approach to a very challenging problem.